Up for debate: remediating feminist media activism in Canada. Issue 1 (2nd January 2018) - Thrift, Samantha C.
Abstract: This analysis examines activists' remediation of a feminist media event, the 1984 televised leadership debate on women's issues, during the 2015 Canadian federal election. Activists framed the 1984 event in campaign materials in commemorative terms, mobilizing a distinctly feminist cultural memory of the nation. Remediating the feminist past produced a discursive disruption of postfeminist constructions of the nation as already gender equal in news coverage of Up for Debate. In this way, women's issues debates act as a barometer of neoliberal entrenchment in Canada.